The effects of human resource management practices on firm productivity: Preliminary evidence from Finland - Derek C. Jones; Panu Kalmi; Takao Kato; Mikko Mäkinen (The Research Institute of the Finnish Economy (ETLA), 2008)
This paper presents the first empirical evidence on the nature and effects of human resource practices (HRM) in the Finnish manufacturing sector. In the analysis, we use the novel survey on HRM practices, based on a representative random sample from the population of the Finnish manufacturing firms who had 50 or more employees in 2005. In the sample, we have firm-level information on several HRM and employee participation practices of 398 firms, which is 38% of the firms in the population and almost 50% of the survey respondents. To study how HRM practices affect the level of firm productivity, we first combined the HRM survey data with financial statement data and then estimated crosssectional and panel data estimators for the Cobb-Douglas production functions. We find that both the incidence of employee participation practices and the incidence of HRM tools have increased in the manufacturing sector from 2002 to 2005. The empirical findings support the view of a positive association with the HRM practices and the level of firm productivity. Perhaps more importantly, however, we find that not all forms of employee financial and decision-making participation practices have favorable productivity effects: consultative committee and profit sharing scheme has a positive effect, but other practices do not have statistically significant effects.
Keywords: M54; J53; L23; 330; new workplace practices; HRM; employee participation; productivity; Personalmanagement; Mitbestimmung; Cobb-Douglas-Produktionsfunktion; Produktivität; Verarbeitendes Gewerbe; Finnland